KẾT QUẢ NGHIÊN CỨU THÀNH PHẦN LOÀI CHIM TẠI KHU BẢO TỒN THIÊN NHIÊN PÙ HOẠT, TỈNH NGHỆ AN NĂM 2018 - Nguyễn, Hồng Phương (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESULTS OF THE RAPID AVIFAUNA SURVEYS IN PU HOAT NATURAL RESERVE, NGHE AN PROVINCE A total of 125 bird species belonging to 39 families and 10 orders have been recorded, of which Passeriformes was the most abundant with 88 species accounting for 70.4%, Piciformes 11 species - 8.8%, Columbiformes 6 species - 4.8%, Accipitriformes and Cuculiformes 5 species - 4%, others order 1 to 3 species, accounting for 11.8%. We confirmed the first record of Collared Treepie for the North Central of Vietnam and adding one more species for the birdlist of Pu Hoat Nature Reserve (Rufous-cheeked Laughingthrush).